You wish - Lethcoe, Jason (Grosset & Dunlap New York, 2007)
When a miserable orphan unknowingly disrupts the balance of power between the magical realms of wishes and curses, he must join forces with the Wishworks Factory to reclaim his errant wish and set things right again